UPAYA MENINGKATAN HASIL BELAJAR SISWA MELALUI METODE PADA MATA PELAJARAN IPA FISIKA KALOR DAN PERPINDAHANNYA KELAS VII - Yogawati, Marlina Indah (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Terbuka, 2023)
Research that aims to determine student learning outcomes using the Discovery Learning learning model to improve critical thinking skills and find out student learning activities on heat material and its transfer, by involving junior high school students grade VII SMP Nurul Amal Keling for the 2022/2023 academic year. PTK is designed in two cycles so that learning objectives can be fulfilled, namely students' critical thinking skills and understanding the concept of heat and its displacement close to everyday life. The supporting instruments used in the study were RPP, LKPD and tests. Tests and LKPD are used to assess students' critical thinking skills and ability to solve problems, both individually and in groups and assess students' level of understanding of heat and its displacement in everyday life. Data collected and presented in the form of understanding, heat formula and application of the concept of heat and its displacement in everyday life.